Psychological Well-Being Of Teachers In Islamic Boarding School: A Qualitative Study Of Work Stress And Mental Health Programs - Annisa Prawati Ningrum; Mulyawan Safwandi Nugraha (Jurnal Manajemen Pendidikan Islam Darussalam, 2026)
This study analyzes the relationship between work stress, mental health programs, and the psychological well-being of Islamic boarding school teachers through an integration of modern psychology and Islamic spirituality. This study used a descriptive qualitative method with a case study approach through in-depth interviews, observations, and documentation analysis. The results show that teacher work stress is triggered by administrative burdens, role conflict, and long working hours, which cause symptoms of physical exhaustion, anxiety, and burnout according to transactional stress and burnout theories. However, this stress can be minimized through social support among teachers and religious coping strategies based on Islamic values, such as dhikr, prayer, and silaturahmi. The mental health program in the Islamic boarding school, although still simple, includes stress management workshops, informal counseling, discussion forums, and collective religious activities. This program serves as a resource that balances teachers' work demands, in line with the Job Demands Resources model. In general, teachers demonstrate good psychological well-being, characterized by self-acceptance, positive social relationships, intrinsic motivation, and a meaningful life purpose. This condition is in accordance with the concept of Psychological Well-Being and the WHO-5 Well-Being Index, and is in line with the Islamic values of qalbun sal?m (healthy heart) and ?uma?n?nah (inner peace). These findings strengthen the understanding that the psychological well-being of Islamic boarding school teachers is shaped by the synergy between modern psychological approaches and Islamic spirituality, while providing a conceptual contribution to the development of a contextual and integrated model of teacher mental health in Islamic educational institutions.